Zoning Potential Halal Tourism Evidence in Indonesia - Pramana, Angga; Sukma R.Ab, Dodi; Zamaya, Yelly; Jayalaksamana, Maghfirah (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
Halal tourism destinations have grown quite significantly, although there are still various weaknesses. This research aims to map the potential of halal tourist destinations in Pekanbaru. This mapping is expected to be a reference for Pekanbaru City to develop the concept of halal tourism in Pekanbaru. The method in this research is the study of documentation, observation, and interviews. This documentation study is also intended to obtain the concept of mapping halal tourism zoning in the city of Pekanbaru. The results show that tourist attractions in Pekanbaru have very good and friendly facilities for visitors to halal tourism which must be linked to mapping. The potential of halal tourist destinations in Pekanbaru can be grouped into historical destinations, nature, shopping centers, mosques, sports centers and restaurants. Several destinations still need to continue to develop supporting facilities to increase the comfort of visitors to halal destinations while in these destinations. The mapping that has been done has a role as a travel route recommendation that makes it easier to direct halal tourists from arrival to returning to their homes.